Performance of sodium chloride, bentonite and conductive cement as grounding enhancement materials - Wan Ahmad, Wan Fatinhamamah; Tan, Kok Heng; Ab Kadir, Mohd Zainal Abidin; Jasni, Jasronita (2015)
A good grounding system is very important in order to protect overall system facilities and equipment. Ground resistance varies with soil types, temperature, moisture content, salt content and compactness of the soil. The main purpose of this study is to compare the performance of three different enhancement materials in combination and individual where the best solution in reducing the grounding resistance is proposed. Fall of potential method is used in this study to measure the ground resistance, where the measurements are done for 182 days, i.e. from 10th October 2010 to 10th April 2011. By applying the separation angle and 62% method, the results showed that the Sodium Chloride backfilled grounding system demonstrated the lowest ground resistance value. The reference ground system on the other hand, had shown the highest ground resistance value. The percentage difference between the two after 182 days is 76.75%. The performance of enhancement materials in ascending order is conductive cement, bentonite, combination and Sodium Chloride. In the consideration of lower ground resistance and cost, it is suggested that bentonite is the best enhancement material to be used in reducing ground resistance values of grounding system in this work.